Potency of two Trichoderma harzianum isolates in liquid and solid organic formula for controlling bacterial wilt on tomato in the field - Loekas Soesanto; Murti Wisnu Ragil Sastyawan; Nina Nurliana; Endang Mugiastuti (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
This research aimed to determine the potency of two Trichoderma harzianum isolates in solid and liquid organic formulas to control bacterial wilt and on growth and yield of tomato in the field. This research was carried out at the Laboratory of Plant Protection and the tomato field at Banteran Village, Sumbang Sub-District, Banyumas Regency at altitude of 600 m above sea level for four months. A randomized block design was used with five replicates. The treatments were control, T. harzianum T10, T. harzianum T215, combination of T. harzianum T10 + T. harzianum T215, and bactericide (a.i. 20% streptomycin sulfate). Variables observed were pathosystem components (incubation period, infection rate, disease intensity, and late populations of the antagonists), growth components (plant height, plant fresh and dry weight, and root fresh and dry weight), yield components (number of fruits, fruit weight), and phenolic compounds analysis qualitatively. The results showed that T. harzianum T10 + T. harzianum T215 was effective to suppress the disease as 58.61%. The treatment of T. harzianum T10 + T. harzianum T215 was effective to increase crop height, fresh weight of plants, dry weight of plants, fresh weight of roots, dry weight of roots, number of fruits and fruit weight as 38.86, 35.37, 51.67, 24.78, 37.41, 40.61, and 53.22%, respectively. All treatments could increase phenolic compound content qualitatively.